First Synoptic Images of FUV Discrete Aurora and Discovery of Sinuous Aurora at Mars by EMM EMUS. Issue 16 (23rd August 2022) - Lillis, Robert J.; Deighan, Justin; Brain, David; Fillingim, Matthew; Jain, Sonal; Chaffin, Michael; England, Scott; Holsclaw, Greg; Chirakkil, Krishnaprasad; Al Matroushi, Hessa; Lootah, Fatma; Al Mazmi, Hoor; et al.
Abstract: We present the first measurements of Mars discrete aurora in the extreme ultraviolet (<110 nm) and the first synoptic aurora images in the far ultraviolet (110–180 nm). Auroral emission is detected in >75% of nightside images, with patterns shifting visibly over 15–20 min. Aurora is observed most frequently in regions of open magnetic topology (where crustal magnetic fields are very weak and/or vertical), with the brightest aurora where crustal fields are strongest. We present the first disk‐averaged spectrum of discrete aurora, with several O, C, and CO features as expected for electron impact primarily on CO2 . We categorize discrete auroral morphology into three types: crustal field aurora, non‐crustal field patchy aurora, and a new type we call "sinuous" aurora, an elongated serpentine structure that stretches thousands of kilometers into the nightside from near midnight in the northern hemisphere. These observations point to a highly dynamic environment in Mars' magnetotail. Plain Language Summary: In this study, we present near‐global images of localized aurora on Mars and the first measurements of these aurora at very short ultraviolet wavelengths (<110 nm). They are caused by energetic electrons from the solar wind smashing into Mars' upper atmosphere. We find auroras in >75% of images, with their patterns shifting visibly over 15–20 min. They are observed most frequently in regions where magnetic fields are very weak or both strong and vertical, with the brightest aurora where magnetic fields are strongest. We present the first disk‐averaged spectrum of these auroras, showing features expected for electrons striking CO2 (the most abundant gas in Mars' atmosphere). We categorize discrete auroral patterns into three types: those near strong vertical crustal magnetic field, patchy aurora near very weak crustal fields, and a new type we call "sinuous, " an elongated serpentine structure that stretches thousands of kilometers into the nightside from near midnight in the northern hemisphere. These observations point to a highly dynamic environment in Mars' nightside space environment. Key Points: We present the first disk measurements of Mars discrete aurora in the EUV end FUV, with the oxygen feature at 130.4 nm being the brightest Auroras are detected in ∼75% of nightside images and are more likely where crustal fields are either very weak or both strong and vertical An elongated, sinuous discrete aurora is discovered, extending far into the nightside. It may be related to the magnetotail current sheet